The impact of tax avoidance and good corporate governance strategies on financial company debt costs - Egi Gumala Sari (Indonesia Accounting Research Journal, 2025)
This study aims to test and analyze the effect of tax avoidance and good corporate governance on the cost of debt in companies in the sub sector of financial holding companies, investment companies and banks listed on the bei during the period 2018-2023. This research uses a quantitative approach with the panel data regression method. The samples used are financial sector companies with sub-sectors of Financial Holding Companies, Investment Companies, and Investment Banks & Trading Intermediaries listed on the Indonesia Stock Exchange in the 2018-2023 period. Research using panel data with panel regression models and data processing software using Eviews. The results of the study are expected to provide an understanding of the effect of tax avoidance and good corporate governance on the cost of debt, as well as the implications for companies and regulators in the financial sector. This research has several limitations, among others: The research was only conducted on financial sector companies in the sub-sectors of Financial Holding Companies, Investment Companies, and Investment Banks & Trading Intermediaries listed on the Indonesia Stock Exchange between 2018-2023. The research focus is limited to tax avoidance and good corporate governance on the cost of debt. Data sources are limited to audited company financial statements. This limitation needs to be considered in interpreting the research results, and can be the basis for further research with a broader scope.